Consumer Shopping Preferences and Social Media Use During Covid-19 Pandemic - Gunaningrat, Rayhan; Purwandari, Suci; Suyatno, Agus; Hastuti, Indra (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2021)
This study empirically investigates the relationship between social media use at home and consumer shopping preferences during Covid-19 pandemic in an emerging country, Indonesia, using survey data. This study focus on popular consumer retail stores including online retail stores such as Tokopedia, Shopee, Lazada and KlikIndomaret, as well as brick-and-mortar retail stores, such as Indomaret, Alfamart, Super Indo, and Transmart. Social media use of popular platforms such as Instagram, Facebook, YouTube, Twitter, Line, and LinkedIn are analyzed. The results of our analysis found that the use of Instagram, Facebook, YouTube, Twitter and LinkedIn at home is associated with consumer shopping preferences at online retail stores such as Tokopedia, Shopee, Lazada, and KlikIndomaret. In addition, our analysis revealed that the use of these social media platforms at home is associated with consumer shopping preferences at brick and mortar retail stores such as Alfamart, Indomaret, and Super Indo. Interestingly, there is no significant association between social media use at home and consumer shopping preferences at Transmart brick-and-mortar stores. Media Richness Theory and Strength of Weak Ties Theory help explain the results of this study. Retail stores need to consider which social media platform is more effective for implementing their marketing strategy. The results of this study can be used as a reference in developing a retail store marketing strategy through social media.